Quality control standardization of the rhizome of curcuma yunnanensis: A comprehensive standardization process - Laloo D.; Hemalatha S.; Prasad S.K. (My University, 2025)
Curcuma yunnanensis (CY) (Zingiberaceae) is a plant having a long flowering season (July-October). It is well morphologically characterized by its lance-shaped leaves having a purplish stripe running down the midrib and greenish coloured rhizome when cut transversely. Pharmacognostical standardization of the rhizome has been evaluated as per WHO guidelines. The dried rhizomes are golden-brown colour and vary in size (2 to 7 cm length and 1 to 2 cm diam.). The histological characteristic of the rhizome shows dissimilarity with other existing Curcuma species. Physico-chemical standards studied are foreign organic matter (0.16% w/w), loss on drying (9.80% w/w), total ash (7.66% w/w), acid insoluble ash (1.70% w/w), water-soluble ash (3.17% w/w), alcohol soluble extractive (8.77% w/w) and water-soluble extractive (7.70% w/w), foaming index (<100), swelling index (4.3) and volatile oil content (0.8%). Powdered characterization showed the presence of starch grains, unicellular covering trichomes and lignified xylem vessels. Phytochemical screening showed the presence of alkaloids, glycosides, phenolics, tannins and steroidal components. Quantitative estimation of total tannins and phenolics was also determined in the ethanolic extract and was found to contain 21.375 and 22.5 mg/g GAE, respectively. The presence of demethoxycurcumin in the CY ethanolic extract was also documented for the first time using HPTLC by comparing with standard curcumin. © 2020, National Institute of Science Communication and Information Resources. All rights reserved.